High species diversity revealed by phylogenetic analysis of the Mexican Tulostoma (Agaricales, Agaricaceae) species - Alcántar, Olivia Rodríguez; Figueroa-García, Darío; Ruiz-Sanchez, Eduardo; Zamora-Tavares, Pilar; Herrera-Fonseca, María De Jesús; Vargas-Ponce, Ofelia (Phytotaxa, 2025)
The genus Tulostoma (Agaricaceae) is characterized by basidiomata that are globose and stiptitate with powdery gleba, and occasionally volvate stipes. Despite their wide distribution, the species diversity and phylogenetic relationships remain poorly understood in Mexico. Using Mexican material, we assessed global Tulostoma diversity and phylogenetic relationships by analyzing ITS and 28S LSU sequences from 130 specimens (including 17 newly sequenced Mexican samples). Our phylogenetic reconstruction, incorporating both molecular and morphological data, revealed significant discrepancies with previous morphology-based identifications of Mexican specimens. The analysis identified six new species (Tulostoma perezdelarosae, T. cristatum, T. grulloense, T. centinelaense, T. neoleonense, and T. obledoi) and highlights the pseudocryptic nature of many Tulostoma species due to their high morphological variability. Our phylogenetic analysis revealed an unexpected result: the six recognized genera of Tulostomateae (Queletia, Schizostoma, Chlamydopus, Morganella, Battarrea and Battarreoides) were nested within the Tulostoma clade. These findings substantially advance our understanding of Tulostoma systematics while demonstrating the necessity of molecular approaches for accurate species delimitation in this challenging genus.